2010
DOI: 10.2353/ajpath.2010.091278
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Tract Disorder in Natriuretic Peptide Receptor B Gene Mutant Mice

Abstract: Natriuretic peptide receptor B (NPR-B), which has high affinity for C-type natriuretic peptide (CNP) and synthesizes intracellular cGMP, may be involved in gastrointestinal tract (GIT) regulation. A mutant allele of the NPR-B-encoding gene (Npr2) is responsible for the phenotype of the short-limb dwarfism (SLW) mouse. Homozygosity for this autosomal-recessive gene (slw/slw) leads to dwarfism and death before weaning because of milk retention in the stomach and intestinal distention. To elucidate the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…When CNP binds to NPR-B, it could activate GC to catalyze the transformation of cGMP from GTP and then cause a relaxation of the gastric and colonic smooth muscles. [17][18][19] There was a report which confirmed that inhibitory effect of CNP on gastric smooth muscle was strengthened in diabetic rat via up-regulation of cGMP, 20 are the most common isoforms in GI tract, and PDE3 is a main regulator of murine gastrointestinal circular muscle contraction, while higher concentration of PDE2 could partly influence the gut motility. 22,23 Cai et al 24 confirmed only the expression level of PDE3 was decreased in gastric smooth muscle of diabetic rats.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…When CNP binds to NPR-B, it could activate GC to catalyze the transformation of cGMP from GTP and then cause a relaxation of the gastric and colonic smooth muscles. [17][18][19] There was a report which confirmed that inhibitory effect of CNP on gastric smooth muscle was strengthened in diabetic rat via up-regulation of cGMP, 20 are the most common isoforms in GI tract, and PDE3 is a main regulator of murine gastrointestinal circular muscle contraction, while higher concentration of PDE2 could partly influence the gut motility. 22,23 Cai et al 24 confirmed only the expression level of PDE3 was decreased in gastric smooth muscle of diabetic rats.…”
Section: Discussionmentioning
confidence: 90%
“…As a crucial peptide hormone of the natriuretic peptide family, CNP could be secreted in GI tissue and preferentially binds to its specific receptor NPR‐B, which was distributed in the GI smooth muscle layer. When CNP binds to NPR‐B, it could activate GC to catalyze the transformation of cGMP from GTP and then cause a relaxation of the gastric and colonic smooth muscles . There was a report which confirmed that inhibitory effect of CNP on gastric smooth muscle was strengthened in diabetic rat via up‐regulation of cGMP, but the effect of CNP on colon in the diabetic model has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Isometric contraction test of oviductal smooth muscle was performed as described previously (Sogawa et al 2010, Ning et al 2014) with some modifications. Briefly, the ampullary (n = 5) and isthmic (n = 6) tissues of bovine oviducts obtained from cows after ovulation were cut open and 3-mm-length strips were prepared.…”
Section: Isometric Contraction Testmentioning
confidence: 99%
“…Expression and/or activity of GC-A, GC-B, and their ligands can be found in the intestinal tract of rabbits, rodents, and humans in a wide variety of cell types including IECs, smooth muscle, myenteric and submucosal neurons, myofibroblasts and the interstitial cells of Cajal (ICC) [2 , [42][43][44][45]. ANP/GC-A is a classical regulator of sodium flux in the intestine and has recently been shown to regulate CFTR expression in IECs [43].…”
Section: Intestinal Transmembrane Guanylate Cyclase Receptors: Intestmentioning
confidence: 99%
“…CNP/GC-B regulates circular smooth muscle relaxation and may act directly in the ICC to control small bowel pacemaker currents [44,45]. Notably, although genetic deletion of GC-B in mice does not result in a severe gastrointestinal phenotype, two separately reported GC-B truncation mutants result in a lethal loss of intestinal motility [42,46,47]. Best described is the short-limb dwarfism (slw) mouse which lacks the intracellular domain of GC-B.…”
Section: Intestinal Transmembrane Guanylate Cyclase Receptors: Intestmentioning
confidence: 99%